UPAYA PENINGKATAN DAYA INGAT ANAK MELALUI PERANCANGAN APLIKASI MULTIMEDIA BAGI ANAK USIA 5 -6 TAHUN - Saidatul Mar’ah (STEKOM PRESS, 2017)
After doing research in KB and TK Anak Pintar, it can be seen that there are obstacles that are owned by TK B teaching teachers in delivering the material. The obstacle faced is where children are easily bored with conventional learning methods used by teachers plus there is no learning media at the school. To anticipate these obstacles, learning media are needed that can increase children's interest in learning and can eliminate the boredom of conventional learning. The purpose of this study is to find out how and the benefits of Macromedia Director MX 2004 in the world of education. The method used in the Research and Development (research and development) method, starts from (1) potential and problems, (2) data collection, (3) learning media design, (4) learning media validation, (5) revision of learning media, ( 6) trial of learning media, and (7) application. The results showed that the developed media had fulfilled the requirements and fulfilled the requirements to be used, this was seen from the results of the validation carried out by media experts namely 90% and material experts 92.5% and Kindergarten B teachers 92.5%. By displaying 6 learning materials that are accompanied by 5 questions in each material, it is also equipped with instructions for use, profiles of teachers and KB staff and Kindergarten Smart Children and also vision and mission.